A Pilot Trial of Platelets Stored Cold versus at Room Temperature for Complex Cardiothoracic Surgery. (December 2020) - Strandenes, Geir; Sivertsen, Joar; Bjerkvig, Christopher K.; Fosse, Theodor K.; Cap, Andrew P.; del Junco, Deborah J.; Kristoffersen, Einar Klæboe; Haaverstad, Rune; Kvalheim, Venny; Braathen, Hanne; Lunde, Turid Helen Felli; Hervig, Tor; et al.
Abstract : Background: This pilot trial focused on feasibility and safety to provide preliminary data to evaluate the hemostatic potential of cold-stored platelets (2° to 6°C) compared with standard room temperature–stored platelets (20° to 24°C) in adult patients undergoing complex cardiothoracic surgery. This study aimed to assess feasibility and to provide information for future pivotal trials. Methods: A single center two-stage exploratory pilot study was performed on adult patients undergoing elective or semiurgent complex cardiothoracic surgery. In stage I, a two-armed randomized trial, platelets stored up to 7 days in the cold were compared with those stored at room temperature. In the subsequent single-arm stage II, cold storage time was extended to 8 to 14 days. The primary outcome was clinical effect measured by chest drain output. Secondary outcomes were platelet function measured by multiple electrode impedance aggregometry, total blood usage, immediate and long-term (28 days) adverse events, length of stay in intensive care, and mortality. Results: In stage I, the median chest drain output was 720 ml (quartiles 485 to 1, 170, n = 25) in patients transfused with room temperature–stored platelets and 645 ml (quartiles 460 to 800, n = 25) in patients transfused with cold-stored platelets. No significant difference was observed. The difference in medians between the room temperature– and cold-stored up to 7 days arm was 75 ml (95% CI, −220, 425). In stage II, the median chest drain output was 690 ml (500 to 1, 880, n = 15). The difference in medians between the room temperature arm and the nonconcurrent cold-stored 8 to 14 days arm was 30 ml (95% CI, −1, 040, 355). Platelet aggregation in vitro increased after transfusion in both the room temperature– and cold-stored platelet study arms. Total blood usage, number of adverse events, length of stay in intensive care, and mortality were comparable among patients receiving cold-stored and room temperature–stored platelets. Conclusions: This pilot trial supports the feasibility of platelets stored cold for up to 14 days and provides critical guidance for future pivotal trials in high-risk cardiothoracic bleeding patients. Abstract : No significant difference was observed between cold-stored and room temperature–stored platelets for hemostatic function assessed by chest drainage, total blood usage, platelet function, and clinical outcomes. This pilot trial supports the potential feasibility of cold-stored platelets for clinical use and provides potential guidance for future pivotal trials.Supplemental Digital Content is available in the text.